18F-FDG PET/CT for staging and response assessment of primary parotid MALT lymphoma with multiple sites involvement: A case report. Issue 5 (February 2019) - Ren, Yixuan; Huang, Lele; Han, Yuping; Cui, Zhencun; Li, Jicheng; Dong, Chi; Liu, Jiangyan
Abstract: Rationale: Mucosa-associated lymphoid tissue (MALT) lymphoma is an extranodal low-grade B cell lymphoma that generally exhibits an indolent clinical course. Currently, the application of 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) in MALT lymphoma is still controversial. Herein, we reported a case of using 18 F-FDG PET/CT for staging and response assessment of primary parotid MALT lymphoma with multiple sites involvement. As far as we know, there are no similar case reports have been published before. Patient concerns: A 71-year-old woman, who received mass resection twice during the past 2 years due to the repeatedly relapse of facial painless masses and diagnosed as reactive lymphoid hyperplasia by pathologic tests. However, the pathological diagnosis was then changed to primary parotid MALT lymphoma after left parotidectomy operation because of a new mass found in her left parotid. Four months later, the right eyelid of the patient swelled with a blurred vision. Then, 18 F-FDG PET/CT scan was performed for staging, and the imaging results showed an abnormal increase of 18 F-FDG uptake in multiple sites including bilateral ocular adnexal, lungs, pleura, occipital subcutaneous tissue, left kidney, and lymph nodes. Diagnoses: The patient was diagnosed as primary parotid MALT lymphoma with Ann Arbor stage of IVA based on the 18 F-FDG PET/CT findings. Interventions: The patient received 4 cycles of chemotherapy, followed by a partial metabolic remission (PMR), which was determined by interim 18 F-FDG PET/CT, and finally additional 2 cycles of chemotherapy. Outcomes: The follow-up study illustrated that the patient had been alive and doing well at 12 months after chemotherapy. Lessons: Although MALT lymphoma normally localizes in the primary organs, the involvement of multiple organs and lymph nodes is possible. The use of PET/CT demonstrated significant clinical values in the accurate staging and response assessment of 18 F-FDG-avid MALT lymphoma. It is potentially useful for indicating the progress and transformation of MALT lymphoma, and guidance in localization of pathological biopsy. It is also helpful for clinicians to choose reasonable treatment strategy and improve the prognosis of patients.